PERAN KEPALA SEKOLAH DAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN SUASANA KEBERAGAMAAN PADA PESERTA DIDIK - Ahmad Habibi, (UNISAN JURNAL, 2024)
This research aims to determine (a) the role of teachers (b) students' religious behavior and, (c) the benefits of students' religious behavior. This research uses a qualitative descriptive research approach regarding the role of teachers in fostering religious behavior by collecting data from primary data sources, namely teachers and students, while secondary sources include observation, interviews and documentation with data collection techniques, namely data reduction and data presentation. and verify in SDS. IT Cipta Insan Cendikia. The role of the teacher at SMA Negeri 3 Jambi City in this research was quite good in terms of the guidance and assistance provided by the SDS IT Cipta Insan Cendikia teacher. This can be seen in the teaching and learning process that takes place at SDS IT Cipta Insan Cendikia. This can be seen when before starting the learning process, it begins with reading the Al-Quran, praying, carrying out dhuha prayers during breaks. , charity or almsgiving if available. one of the female students who experienced a disaster (a family member died) every Friday the female students carry out donations carried out by the OSPA School, especially the female students attend Rohis recitation every Friday. The role of teachers as facilitators is seen during Islamic holidays, namely paying zakat in the month of Ramadan, and students become members of the Amil Zakat committee organized by the school and this activity becomes a mandatory school program. Apart from that, the religious behavior of the students is to carry out congregational prayers at the mosque, namely the noon prayer. Most of the religious behavior of students at SMA Negeri 3 Jambi City is seen in daily life in the school environment, although there are still a small number of students who are not good at carrying out routine activities implementing religious behavior. Keywords: Teacher's Role, Coaching, Religious Behavior